Research on in-situ observation system of seabed boundary layer based on self-potential measurement. Issue 6 (October 2020) - Fan, Zhihan; Jia, Yonggang; Guo, Xiujun; Xu, Haibo; Xue, Liang; Feng, Yasheng; Wu, Shiguo; Jin, Sun; Lu, Jingan; Wang, Ziyu
Abstract: The submarine boundary layer is a dynamically changing strip located near the seabed interface. The dynamic change process involves the resuspension and redeposition of sediments, which has an important impact on the transportation of seafloor sediments and the transport of offshore chemical substances. Based on the self-developed self-potential monitoring device, the stability of the device and the characteristics of the seabed and the bottom layer of the sea floor with different textures were tested through laboratory experiments. The results show that the self-developed self-potential monitoring probe has high corrosion resistance, good electrode stability, and guaranteed measurement accuracy. The self-potential measurement can clearly identify the position of the seabed interface, and can judge seabed sediments by positive and negative anomalies. Nature, the sandy seabed is negative anomaly (about -8 mv), the clayey seabed is positive anomaly (about 10 mv). The concentration of solid suspended particles in the seawater and the self-potential difference between the seawater and the seabed appear relatively good linear relationship, the smaller the difference, the greater the concentration of solid suspended particles. The re-deposited sediment changes its self-potential under the influence of material composition and pore structure, but this effect gradually decreases as the consolidation time increases. Therefore, the spontaneous potential measurement can better reflect the dynamic changes of the seafloor sediments, and effectively monitor the dynamic changes of the seafloor boundary layer. It provides a new method for the in-situ observation of the dynamic changes of the submarine boundary layer.